AGE-RELATED FEATURES OF THE LIMBIC SYSTEM IN THE FORMATION OF BEHAVIOR - Saidmurodova Zulfiya Gayratjonovna; Alimova Ozoda Bekmurodovna (Web of Journals Publishing, 2025)
The limbic system is a complex of structures within the central nervous system that plays a crucial role in regulating emotion, motivation, memory, and behavior. It occupies a central position in the control of human behavior. By integrating emotional states, memory, motivation, and instinctive reactions, the limbic system enables the organism to adapt to both external and internal conditions. This article analyzes scientific literature on the age-related development of behavior, the morphological and functional maturation of the limbic system, and the significance of maintaining balance between the limbic system and the prefrontal cortex in ensuring emotional stability and conscious behavioral regulation.
Keywords: Limbic system, prefrontal cortex, motivation, amygdala, aggression, hippocampus, amygdaloid body, hypothalamus, cingulate gyrus.